PEMBERDAYAAN MASYARAKAT DESA OLELE MELALUI PELATIHAN PEMBUATAN NUGET IKAN NIKE KELOR DAN CAKE KELOR - Margaretha Solang; Masra Latjompoh (Jurnal Pengabdian Masyarakat Pinang Masak, 2020)
Olele village in Kabila Bone district is among the villages located in the southern coastal area of the province of Gorontalo. The majority of people there work as fishermen and farmers. Nike fish (Awaous melanocephalus) and moringa (Moringa oleifera) are the common natural resources in Olele village. The objective of this mentoring project was to enhance the food processing skills of the local community by disseminating steps in processing moringa nike fish nugget and the potential of the leaves of a moringa as the ingredient of moringa leaf cake. Its steps included 1) preparation, 2) program implementation, and 3) evaluation. Based on the results, the mentoring program contributed to the enhancement of both knowledge and skills of the participants in processing nugget of moringa nike fish. The participants were also aware of the potential of the leaf moringa as an ingredient of a healthy diet. Further, all participants were able to make moringa nike fish nugget and moringa leaf cake. These two food products received a positive reception from all panelists. In the end, all participants would improve all of the food products through their home-based food business. This was also to support the food business program in their village.